Physiotherapy Rehabilitation Program in Phase-2 Anterior Cruciate Ligament Reconstruction Recovery: A Case Report - Rizkya, Rinta; Widodo, Agus; Mardianto, Halim (Universitas Muhammadiyah Surakarta, 2023)
Background: Anterior cruciate ligament (ACL) injury is a common knee injury in both the general population and athletes. Structured and systematic and progressive rehabilitation is recommended in the post ACL reconstruction and conservative management, the goal of rehabilitation is to overcome neuromuscular related disorders, muscle strength deficits, joint scope of motion deficits, balance, knee stabilization, motor control and return to sports safely Objective: Physiotherapy rehabilitation program for phase 2 anterior cruciate ligament reconstruction recovery. Methods: The study used the Case Report method which was carried out at the K.R.M.T Wongsonegoro Semarang Hospital on a 25-year-old male patient diagnosed with postoperative ACL reconstruction dextra with complaints of pain in the left knee, swelling and limited knee bending. Results: Physiotherapy intervention in the form of Excercise is able to reduce pain, swelling, increase muscle strength and increase the scope of motion of the knee joint and improve functional activities. Conclusion: Based on research using this Case Report, it shows that the physiotherapy rehabilitation program on ACL reconstruction as a whole obtained the results of changes and improvements.